A study on borrower choice and market competition in Singapore’s moneylending market - Lee, Jasmine Jia Shing (2016)
This paper uses data obtained from Onelyst, an online loan matching platform to study the Singapore moneylending market. We explored two main research questions: what offer terms are borrowers most concerned with when making an offer acceptance decision (Choice Model) and whether lenders compete to offer more favourable loan terms (Competition Model). The Choice Model utilizes the Conditional Logistic Regression Model to understand how borrowers make decisions when faced with multiple loan offers, and the results show that amongst the various offer characteristics available in our data, borrowers are most concerned with the Offer Amount-to-Request Amount Ratio (Offer-Request Ratio), Interest Rate, and Distance between them and the moneylender. The result has regulatory implications, as authorities have mainly focused on regulating the licensed moneylending market via restrictions on interest rates, and have in fact banned the geographic entry of moneylenders; however, our results show that preventing such entry could be undesirable for borrowers. The Competition Model builds on the findings of the Choice Model and examines if lenders compete by lowering Interest Rates and increasing Offer-Request Ratio. We used a Two-Stage Least Squares Regression (2SLS) to correct for omitted variable bias in the Ordinary Least Squares (OLS) Regression. The results were insignificant for Offer-Request Ratio but highly significant for Interest Rate, where the 2SLS estimates show that the marginal offer induced by market competition reduces interest rate significantly, while the marginal endogenous offer has negligible impact. This shows that competition is in fact beneficial to borrowers, and that regulators should reconsider anti-competitive measures in the future.